The practices and politics of making policy: irrigation management transfer in Mexico - Rap, Edwin; Wester, P. (2013)
This article argues that policy making is an interactive and ongoing process that transcends the spatio-temporal boundaries drawn by a linear, rational or instrumental model of policy. We construct this argument by analysing the making of the Irrigation Management Transfer (IMT) policy in Mexico in the early 1990s, focusing on different episodes of its re-emergence, standardisation, and acceleration. During this period a standardised policy package was developed, consisting of a set of specific policy technologies to effect the transfer to Water Users' Associations (WUAs). These technologies were assembled in response to geographically dispersed trials of strength: experiments, consultations and clashes in the field, and negotiations at the national and international level. A newly installed public water authority increasingly succeeded in coordinating the convergence and accumulation of dispersed experiences and ideas on how to make the transfer work. Our analysis shows how this composite package of policy technologies worked to include a network of support and to exclude opposition at different levels, while at the same time stabilising an interpretation of policy-related events. In this way the policy gathered momentum and was 'made to succeed'.